Paradoxes and uncertainties of the Andean economies - Romero Cevallos, Marco (2016)
This article posits that there is a contradiction between the Andean economies' good macroeconomic performance, which has been based on both higher GDP growth rates and lower inflation rates, increased political instability in the Andean Region. The latter of which is fostering the constitution of one of the most conflictive zones in the Americas. In analyzing the Andean economies, the author highlights the limits posed by unemployment rates, which prompt a very paradoxical and fragile situation. Within this context and given the serious doubts in the region about the costs and benefits of the US-Andean Free Trade Agreement, its current negotiations currents negotiations are seen as a serious treat to the Andean Integration process.